On the selective universalism of museum institutions - Remešová, Anna (Romano džaniben, 2023)
Using the National Museum's exposition History of the 20th Century as an example, the text shows the Czech hegemonic museum discourse from which national minorities, specifically the Roma, are excluded. In analyzing such a discourse, the text turns deeper into history to the development of the Czech National Museum and its homogenous understanding of the nation, but also to the broader ways in which the practice of "selective universalism" was adopted from Western European museum institutions. The author then reflects on the possibilities of decolonizing existing museum practice as part of a broader production of knowledge.